Survivors Discovery Robot - Safa, Hadeel; Salawdeh, Amaal (My University, 2017)
Destroyed building after earthquakes or wars is a horrible matter to deal with since it needs a lot of time, cost, labor and lack of safety to find survivors in order to rescue them. So we can apply automated science by using robot to easy our job, from this point of view we build our project to design an automated car as a robot. Our robot car was designed to enter destroyed places regardless on the nature of the difficult way in order to send signal and localize its path by video streaming, also the robot car can turn around even if stumble with destroyed things or flip over, it can continue its way without disruption of its signals or tasks. Another purpose to detect survivals by detect human temperature and send signal back to laptop that will help to rescue people more easily in addition to trace the path to reach them, all of these tasks can be followed by laptop and be controlled by special program with Bluetooth of smart phone.